Early symptoms and long‐term clinical outcomes of distal limb's cutaneous arterio‐venous malformations: a retrospective multicentre study of 19 adult patients. (28th January 2015) - Guillet, A.; Connault, J.; Perrot, P.; Perret, C.; Herbreteau, D.; Berton, M.; Caron, V.; Aubert, H.; Stalder, J.‐F.; Maruani, A.; Barbarot, S.
Abstract: Introduction: Cutaneous arterio‐venous malformations (AVM) are high‐flow vascular malformations made up of a direct link between arteries and veins without intermediary capillary space. 'Distal limb's AVM', which mean involving hands or feet, are rare and their functional prognosis is often poor. Little is known about their early clinical symptoms. The objectives of this study were to identify early clinical symptoms of distal limb's cutaneous AVMs and to determine their long‐term clinical outcome. Methods: A retrospective study was carried out including adult patients who had distal limb's AVM, who were followed up between January 2000 and November 2013 in two regional tertiary care centres. The information was collected from patients' clinical records and completed by a structured telephone questionnaire. Results: Nineteen patients were included in the study: four (21%) with foot AVM and 15 (79%) with hand AVM. The first clinical symptoms were as follows: swelling (47%), pain (47%), one or several venous dilatations (37%) and rarely abnormal skin colour, hyperthermia and pulsating sensation. The median diagnosis delay was 9 years after the onset of first manifestations. Amongst the 17 patients who underwent a treatment, 53% had embolotherapy session(s), 12% surgery and 35% had both. After an average follow‐up of 57.6 months, 31% of the 13 patients contacted who were receiving treatment were in complete remission; 31% had partial remission; 15% had relapse after initial improvement and 23% had treatment failure. Overall, 74% of patients had a serious development of the AVM: 37% had digital or hand amputation, and 42% remained symptomatic and/or unstable. Conclusion: This study suggests that initial manifestations of distal limb's AVMs are discreet and non‐specific, leading to a diagnosis delay of about 10 years, with poor prognosis. Doctors should evoke the diagnosis earlier, when these symptoms are shown: pain and/or swelling, sometimes with a large vein.